A expansão do ensino superior no Brasil: da reforma de 1968 ao anteparo à internacionalização na década de 1980 - Filardi, André Moura Blundi (Universidade Federal de São Carlos, 2019)
This text proposes to analyze the expansion of public and private universities in Brazil in the context that includes the reform of higher Education of 1968, undergoing redemocratization in the decade of 1980, until the mid-1990, when they consolidate trends whose contradictions had been configured in different ways in previous decades. It is a text of history of education that adopts, in its analysis, the historical-dialectical method and its conceptual references, such as those of state and ideology. It seeks to demonstrate in this analysis, the political and economic issues that are inherent to the expansion process of universities and public policies, highlighting their relations with the branch of science and technology. Having as a database: The legislation discussed and approved in the aforementioned historical context; Data and statistics related to expansion; Identification and analysis of the agents involved in this political and economic process; and systematization of the bibliography of specialists in the area. In this way, we seek to perform a retrospective of the conditions that have led to the University of Brazil today and how the national and international scenarios influenced its realization. The possibility of collaborating with the debate on the duality and indissociability between the public and the private and discussions about the models of universities proposed and in force also permeates the hypothesis and analysis. The aim of seeking a master line in the conduction of public policies for higher education and the expansion of the university, that is, to investigate if there existed and how a logic directive for the area in question would be characterized throughout this context. Thus, it is adopted the notion that the state has its political form derived from the commodity form and which is the guarder of the capitalist social relations, which does not prevent, however, for the area of public policies, educational, in particular, to be an area in dispute. Throughout the context studied, it was possible to suggest, through the analysis of data and policies, the balance to one side of this dispute between the public and State University and the Privatist and business University, in favor of the latter.
The expansion of higher education in Brazil: from the 1968 reform to the internationalization of the 1980s
Keywords: Expansão da educação superior brasileira; Público e privado; Políticas educacionais; História da Educação; Expansion of Brazilian higher education; Public and private; Educational policies; History of education; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO